Trachyibana sarawakiensis gen. nov., sp. nov., a remarkable new genus and species from Malaysia (Acari: Uropodina: Trachyuropodidae) - Kontschán, Jenő (Zootaxa, 2015)
A new genus Trachyibana gen. nov. is described and illustrated on the basis of Trachyibana sarawakiensis sp. nov. from Malaysia. The new genus belongs to the family Trachyuropodidae, on the basis of its fringed internal malae, the T-shaped dorsal setae and the position of hypostomal setae h3 (lateral to h1-h2-h4). The new genus differs from the other trachyuropodid genera and species by its lemon-shaped idiosoma, the presence of deep opisthogastric ventral furrows, and the absence of strongly sclerotised dorsal structures.